2008
DOI: 10.1002/jclp.20517
|View full text |Cite
|
Sign up to set email alerts
|

Narrative change in psychotherapy: differences between good and bad outcome cases in cognitive, narrative, and prescriptive therapies

Abstract: This study aimed to clarify the relationship between changes in the patients' narratives and therapeutic outcomes. Two patients were selected from three psychotherapeutic models (cognitive, narrative, and prescriptive therapies), one with good therapeutic outcome and the other with bad therapeutic outcome. Sessions from the initial, middle, and final phases for each patient were evaluated in terms of narrative structural coherence, process complexity, and content diversity. Differences between patients' total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
0
10
0
2
Order By: Relevance
“…Although widely practiced throughout the world, NT remains underresearched (Busch, 2011;Chenail, DeVicentis, Kiviat, & Somers, 2012;Etchison & Kleist, 2000). Some qualitative process research studies (Matos, Santos, Gonçalves, & Martins, 2009;Moreira, Beutler, & Gonçalves, 2008) and several case studies (Betchley & Falconer, 2002;Cashin, 2008;da Costa, Nelson, Rudes, & Guterman, 2007;Draucker, 1998;Kropf & Tandy, 1998;Nylund, 2002;Palgi & Ben-Ezra, 2010;Rothschild, Brownlee, & Gallant, 2000;Young, 2008) suggest positive outcomes for a wide range of problems and disorders. However, only one of these qualitative studies (Kropf & Tandy, 1998) has addressed the effectiveness of NT for depression, and none have done so in a controlled clinical trial.…”
mentioning
confidence: 99%
“…Although widely practiced throughout the world, NT remains underresearched (Busch, 2011;Chenail, DeVicentis, Kiviat, & Somers, 2012;Etchison & Kleist, 2000). Some qualitative process research studies (Matos, Santos, Gonçalves, & Martins, 2009;Moreira, Beutler, & Gonçalves, 2008) and several case studies (Betchley & Falconer, 2002;Cashin, 2008;da Costa, Nelson, Rudes, & Guterman, 2007;Draucker, 1998;Kropf & Tandy, 1998;Nylund, 2002;Palgi & Ben-Ezra, 2010;Rothschild, Brownlee, & Gallant, 2000;Young, 2008) suggest positive outcomes for a wide range of problems and disorders. However, only one of these qualitative studies (Kropf & Tandy, 1998) has addressed the effectiveness of NT for depression, and none have done so in a controlled clinical trial.…”
mentioning
confidence: 99%
“…As noted in Urban, Hargraves, et al (this volume), each of these outcomes enhances the adaptive capacity of the program, enabling the program team greater flexibility to co‐evolve with their environments. These outcomes mirror two of the primary outcomes of psychological counseling: a reformulated, co‐constructed personal narrative that enables a client to better adapt and function within their environment (Moreira, Beutler, & Gonçalves, 2008), and a more developed evaluative mindset, internalized from skilled questions asked by the counselor, that enables the client to go forward, learning and adapting while using this new mindset (Dobson & Dobson, 2018).…”
Section: Relational Parallels Between Rse and Counselingmentioning
confidence: 92%
“…In other research studies using the NA-Grid and the above-mentioned coding systems for the analysis of narrative process, structure, and content (NSCCS, PCCS, and CMCS), respectively, clients' self-narratives have been assessed during the initial, middle, and final stages of the therapeutic process by comparing cases of poor and good therapeutic results. These studies have shown a greater multiplicity of content, a greater structural narrative coherence, and a greater complexity of the narrative process in clients' self-narratives after a successful therapeutic process (Botella & Cutura, 2015;Moreira, Beutler, & Gonçalves, 2008). In another research line, Gonçalves and his team have used the IMCS to study the different moments in the therapeutic process, attending to those segments when clients show signs of change (innovative moments) or, in contrast, ambivalence to change (ambivalence) with regard to the content of their problematic self-narrative.…”
Section: Analysis Of Self-narratives In Psychotherapymentioning
confidence: 99%
“…In other research studies using the NA-Grid and the above-mentioned coding systems for the analysis of narrative process, structure, and content (NSCCS, PCCS, and CMCS), respectively, clients’ self-narratives have been assessed during the initial, middle, and final stages of the therapeutic process by comparing cases of poor and good therapeutic results. These studies have shown a greater multiplicity of content, a greater structural narrative coherence, and a greater complexity of the narrative process in clients’ self-narratives after a successful therapeutic process (Botella & Cutura, 2015 ; Moreira, Beutler, & Gonçalves, 2008 ).…”
Section: Introductionmentioning
confidence: 99%